Minimal hepatic encephalopathy - from cirrhosis to neurological disorders - Jarmołowicz, Jakub; Boczar, Agata; Dryja, Patryk; Solisch, Sven; Stawicka, Izabela; Orzołek, Izabela (Journal of Education, Health and Sport, 2024)
Introduction and aim Minimal hepatic encephalopathy (MHE) is a subtle but significant brain dysfunction resulting from chronic liver damage, with symptoms that can be difficult to detect. It affects patients' quality of life by causing problems with concentration, memory, and motor coordination. Untreated MHE may progress to more severe neurological disorders, such as overt hepatic encephalopathy. The importance of this condition lies in its impact on patients' daily functioning and the increased risk of accidents, particularly in situations requiring quick responses, such as driving.Neurological symptoms caused by the disease are potentially reversible with treatment. Materials and Methods Available literature from the PubMed and Google Scholar databases was reviewed using the following keywords: "minimal hepatic encephalopathy," "hepatic encephalopathy," "cirrhosis," and "SIBO." Conclusion The significance of Minimal Hepatic Encephalopathy is crucial from the perspective of preventing further progression and the onset of overt hepatic encephalopathy, as well as improving the quality of life for our patients. Patients and their families are often unaware of the condition, and the cognitive impairments are frequently underestimated. Enhancing diagnostic methods would enable physicians to identify these patients more promptly.